Implementasi Pembelajaran Yang Berpusat Pada Keragaman Anak Dan Pengelolaan Kelas Inklusif Yang Ramah - Elsa Rahmah Saypani; Nurhalizah Nurhalizah; Opi Andriani (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research aims to find out whether creativity will not appear in students who do not have high motivation, curiosity and imagination. Skills education for students can shape students into more creative children. then the management carried out by child-friendly schools in improving student character. Classroom conditions have a big role in the learning process and outcomes. The classroom environment influences what students learn. analyzing the classroom will allow them to anticipate or explain the problems they are experiencing. The method used is a quantitative method used to research the condition of natural objects.